2018
DOI: 10.1186/s42492-018-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent photoacoustic and ultrasound microscopy with a coaxial dual-element ultrasonic transducer

Abstract: Simultaneous photoacoustic and ultrasound (PAUS) imaging has attracted increasing attention in biomedical research to probe the optical and mechanical properties of tissue. However, the resolution for majority of the existing PAUS systems is on the order of 1 mm as the majority are designed for clinical use with low-frequency US detection. Here we developed a concurrent PAUS microscopy that consists of optical-resolution photoacoustic microscopy (OR-PAM) and high-frequency US pulse-echo imaging. This dual-moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For peripheral vascular visualization, B. Rao et al reported an optical resolution-PAM (OR-PAM) system to visualize mouse ear microvasculatures [ 32 ]. A dual-modality imaging system combining PAM with USI was reported by Y. Tang [ 33 ] to achieve anatomical and functional information of a mouse’s hind paw. Moreover, aiming towards human implementation, a PAM-based system for human peripheral arteries was developed [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For peripheral vascular visualization, B. Rao et al reported an optical resolution-PAM (OR-PAM) system to visualize mouse ear microvasculatures [ 32 ]. A dual-modality imaging system combining PAM with USI was reported by Y. Tang [ 33 ] to achieve anatomical and functional information of a mouse’s hind paw. Moreover, aiming towards human implementation, a PAM-based system for human peripheral arteries was developed [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging biomedical imaging technique, optical-resolution photoacoustic microscopy (OR-PAM) has a sub-cellular resolution, rich optical absorption contrasts, and label-free imaging ability [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Fast speed is of great importance for improving throughput and the study of physiological or pathological changes in vivo, such as brain activities, drug responses, and tumor metastasis processes, et al [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%